Development of Bioinformatic Methods to Determine Chemical Differences Between Nematode Species - Chauhan, Veeren (2022)
The metabolome is the complete set of small-molecule chemicals that are produced during metabolism and is an indicator of cellular activity and the physiological state of an organism. Understanding the complexities and impact of an organism’s complete metabolome, as well as variation between organisms has proven challenging. However, by studying the complete anatomy of an organism, whilst preserving biological complexity, can dramatically improve the amenability to analysis by studying smaller and simpler model organisms such as nematodes, e.g., Caenorhabditis elegans and Pristionchus pacificus. Furthermore, recent technological advances in surface sensitive mass spectrometry, such as the 3D-OrbiSIMS, have made it possible to not only characterise the entire metabolome of an organism, but to also spatially locate where metabolites anatomically originate, to a high spatial and mass accuracy. Therefore, the overarching aim of this study is to develop apply and evaluate bioinformatic methods for 3D-OrbiSIMS metabolome datasets for nematodes C. elegans and P. pacificus to separate species based on their mass spectra.